Assessing the risk from the depleted uranium weapons used in Operation Allied Force - Liolios, Th. E. (HNPS Advances in Nuclear Physics, 2019)
The conflict in Yugoslavia has been a source of great concern for the neighboring countries, about the radiological and toxic hazard posed by the alleged presence of depleted uranium in NATO weapons. In the present study a worst-case scenario is assumed mainly to assess the risk for Greece and other neighboring countries of Yugoslavia at similar distances . The risk of the weapons currently in use is proved to be negligible at distances greater than 100 Km. For shorter distances classified data of weapons composition are needed to obtain a reliable assessment.